Fundamentals of communication systems - Proakis, John G. (Pearson Prentice Hall, 2005)
Introduction - Signals and linear systems - Amplitude modulation - Angle modulation - Probability and random processes - Effect of noise on analog communications systems - Analog-to-digital conversion - Digital modulation in an additive white gaussian noise baseband channel - Digital transmission through bandlimited awgn channels - Transmission of digital information via carrier modulation - Selected topics in digital communications - An introduction to information theory - Coding for reliable communications.